ANALISIS DAMPAK PEMEKARAN WILAYAH KABUPATEN TERHADAP PERKEMBANGAN WILAYAH DAERAH OTONOMI BARU (Studi Kasus DOB Buton Utara Pemekaran dari Kabupaten Muna) - Mitra Sanjaya; R. Marsuki Iswandi; La Ode Geo (Universitas Halu Oleo, 2019)
This study aims to determine the development of Economic Performance in North Buton Regency; knowing the progress of the North ButonRegency Public Service Performance; and knowing the Development of Regional Infrastructure as a basic service facility in North Buton Regency consisting of 6 (six) Subdistricts, that is Kulisusu, Bonegunu, Kulisusu Barat, Kulisusu Utara, Kambowa, and Wakorumba. This study uses an analysis of the development of regional economic performance, analysis of public service performance, and analysis of regional infrastructure development. The results showed that (1) the average development of GRDP on the basis of constant prices before expansion is 5,52 percent and after expansion of 8.23 percent and the average growth rate of Regional Original Income has grown by 16,03 percent; (2) The ratio of the availability of educational facilities for elementary and junior high school levels before expansion is 73.61 percent while after division is 78,32 percent and the availability of health facilities before pemekaran is 5,5 percent while after division is 12.5 percent; (3) growth in the number of education facilities before expansion by 3,7 percent and after division of 4.4 percent, the development of the number of health facilities before pemekaran was 6.1 percent and after expansion of 15,3 percent, the development of religious facilities before expansion was 2,7 percent and after expansion 3,5 percent, and road infrastructure the average growth before expansion is a paved road of 6 percent and not paved 8,54 percent, while after expansion the average paved road growth is 34.89 percent, while the average growth of non-asphalt roads is 17,83 percent. Keywords: Economic Performance, Public Service, and Regional Infrastructure